ARIA e Interactive Access: projetando chatbots para idosos - Ribeiro, Carlos Nery; Oliveira, Cynthya Letícia Teles de; Araujo, Lucas Padilha Modesto de; Rodrigues, Kamila Rios da Hora; Manzato, Marcelo Garcia (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2024: Anais Estendidos do XXX Simpósio Brasileiro de Sistemas Multimídia e Web, 2024)
Elderly individuals represent a significant portion of the population, and trends indicate that this number will increase at an accelerating rate. The elderly often face challenges when interacting with conversational systems, whether due to a lack of familiarity or age-related limitations, such as reduced visual acuity and dexterity. Therefore, it is essential to consider the needs of the elderly when designing these systems. In this work, we present the Assistente de Recomendação e Interação Acessível (ARIA), an accessible chatbot for the elderly that provides recommendations for cultural content, and Interactive Access, a set of guidelines for building accessible chatbots for the elderly. Performance and usability tests were conducted on both artifacts, based on Nielsen’s heuristics. The artifacts showed positive results, pointing the next steps for studies with elderly users.